Teaching Writing Through Telegram Bot: The Impact on Students Writing Performance - Syahreza; Hartina, St. (Universitas Islam Ahmad Dahlan (UIAD), 2023)
The widespread use of mobile device technology and the release of new mobile device applications like Telegram offers a new innovation in integrating technology in language learning. Accordingly, this study intends to evaluate the Telegram BOT's efficacy in enhancing writing abilities at a high school in Palopo, South Sulawesi, Indonesia . It applied pre-experimental with a single group pre- and post-test design as its focal point. The population of this study is 36 first-grade students and took 14 students as the sample randomly. The data was analyzed by using SPSS 22 described statistically and evaluated. The result reveals that the use of telegram bot effective to enhance the students’ writing performance. It is proved that the student's mean score in post test (83, 79) was greater than in pre-test (64, 79) and the significance value (Sig. 2-tailed) is 0.000<0.05. It indicated that using the Telegram BOT Application as a learning medium improves the writing performance. Students can learn independently via Telegram BOT because the material has been provided all with detailed instructions in one of its features called Bot API.